The Effect of Palm Kernel Cake Thickness as a Culture Medium on the Growth and Production of Maggots (Hermetia illucens) - Eldy Marnanda Putra Keliat; Agusnimar Agusnimar; Febry Ferdiyanto Purba (Jurnal Perikanan dan Kelautan, 2026)
Hermetia illucens larvae, commonly known as Black Soldier Fly (BSF) maggots, are rich in protein and fat, making them an excellent alternative feed for fish. Utilizing them as a fish feed source and as a bio-machine for waste processing requires cultivating maggots. This study was conducted for 30 days, from February 6 to March 6, 2024, at the Fish Seed Center (BBI) of the Faculty of Agriculture, Riau Islamic University, Pekanbaru. The method used was a completely randomized design (CRD) with 5 treatments and 3 replicates, namely, P1 = palm kernel meal thickness (5 cm), P2 = 7 cm, P3 = 9 cm, P4 = 11 cm, and P5 = 13 cm. The study's results showed the best results in treatment P5, with a weight gain of 0.252 g, a length gain of 1.83 cm, a daily growth rate of 0.00351%, and an average production of 967 g. The best culture medium content test results were obtained from P5, with water content of 29.74%, protein of 36.60%, fat of 4.31%, carbohydrates of 1.31%, and crude fiber of 2.13%. The environmental parameters during the study were a temperature range of 35.7 to 41.2 °C, a humidity range of 70-96%, and a pH range of 6.3-6.5.